Character-Based Management Strategies in Islamic Education: Comparing Madrasah Policies in Indonesia and Malaysia: (Strategi Manajemen Pendidikan Islam Berbasis Karakter: Studi Perbandingan Kebijakan Madrasah di Indonesia dan Malaysia) - Asyfah Laily Fauziah; Muhammad Yusuf; Aulia Putri Rohmawati; Ahmad Syukri (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
This study aims to analyze and compare character-based Islamic education management strategies in madrasah institutions in Indonesia and Malaysia. Utilizing a Systematic Literature Review (SLR) and comparative analysis approach, this research explores how education policies in both countries integrate Islamic values as a foundation for student character development. The results indicate that Indonesia, through the Merdeka Curriculum, emphasizes creativity, independence, and the strengthening of religious Pancasila student profiles. Meanwhile, Malaysia implements a structured national curriculum standard integrating naqliyyah and aqliyyah sciences, supported by significant government regulatory backing. The similarity between the two countries lies in positioning Islamic education as the primary instrument for instilling values of honesty, responsibility, and integrity. Significant differences were found in curriculum load and the flexibility of student interest pathways, where the Malaysian system tends to be more focused on relevant subjects compared to Indonesia's broader scope. These findings emphasize the importance of synergy between government policies, teacher role modeling, and social environment support in the successful internalization of Islamic character.